Knowledge networks in the German bioeconomy: Network structure of publicly funded R&D networks - Kristina Bogner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2019)
Aiming at fostering the transition towards a sustainable knowledge-based Bioeconomy (SKBBE), the German Federal Government funds joint and single research projects in predefined socially desirable fields as, for instance, in the Bioeconomy. To analyse whether this policy intervention actually fosters cooperation and knowledge transfer as intended, researchers have to evaluate the network structure of the resulting R&D network on a regular basis. Using both descriptive statistics and social network analysis, I investigate how the publicly funded R&D network in the German Bioeconomy has developed over the last 30 years and how this development can be assessed from a knowledge diffusion point of view. This study shows that the R&D network in the German Bioeconomy has grown tremendously over time and thereby completely changed its initial structure. While from a traditional perspective the development of the network characteristics in isolation seems harmful to knowledge diffusion, taking into account the reasons for these changes shows a different picture. However, this might only hold for the diffusion of mere techno-economic knowledge. It is questionable whether the artificially generated network structure also is favourable for the diffusion of other types of knowledge, e.g. dedicated knowledge necessary for the transformation towards an SKBBE.
urn:nbn:de:bsz:100-opus-16077
Keywords: 330; knowledge; dedicated knowledge; knowledge diffusion; social networks; R&D networks; Förderkatalog; sustainable knowledge-based Bioeconomy (SKBBE)